1979
DOI: 10.1093/ajcp/72.5.785
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous Hypertrophy of the Cardiac Interatrial Septum: A Report of 38 Cases and Review of the Literature

Abstract: Thirty-eight cases of lipomatous hypertrophy of the cardiac interatrial septum are presented and analyzed, together with those previously reported. Available data indicate that this entity is more likely to be seen in the seventh to eighth decade of life, in Caucasians, and with age-associated increases of epicardial fat. It differs from cardiac lipoma, which is a true neoplasm occurring in a younger age group. It is probably more frequent than reported as it is usually not looked for. Atrial arrhythmias somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 0 publications
4
37
0
2
Order By: Relevance
“…In most patients, this condition is completely asymptomatic but it may predispose to the development of atrial arrhythmias and conduction disturbances. Although a possible link between this abnormality and stroke cannot be ruled out, this finding has only been reported in 1 published case of stroke [2]. The most plausible cause of atrial fibrillation seen in our patient is the lipomatous hypertrophy of the IAS, since no cardiac disease was noted and supraventricular arrhythmias have been recognized in approximately half of the patients in whom this abnormal- ity was reported [3].…”
mentioning
confidence: 55%
“…In most patients, this condition is completely asymptomatic but it may predispose to the development of atrial arrhythmias and conduction disturbances. Although a possible link between this abnormality and stroke cannot be ruled out, this finding has only been reported in 1 published case of stroke [2]. The most plausible cause of atrial fibrillation seen in our patient is the lipomatous hypertrophy of the IAS, since no cardiac disease was noted and supraventricular arrhythmias have been recognized in approximately half of the patients in whom this abnormal- ity was reported [3].…”
mentioning
confidence: 55%
“…Invariably, even once the diagnosis is done, the true relationship between the mass and its symptoms remains elusive [9]. In the case reported here, we were able to find a specific cause for one of the classical cardiac symptoms of atrial lipoma: the atrial arrhythmia.…”
mentioning
confidence: 67%
“…The mass occasionally has a pseudoencapsule, supplied by surrounding structures (the fossa ovalis, the atrial wall, the interatrial sulcus, the pericardium of the transverse sinus or the posterior atrioventricular groove) [9]. J.T.…”
mentioning
confidence: 99%
“…After its first postmortem description by Prior in 1964, 3 about 200 cases have been reported, but there is speculation that in reality, the incidence is much higher. Reyes et al 4 found the condition in approximately 1% of autopsy cases, whereas analyses of transthoracic echocardiography by Pochis et al 5 revealed LHIS in as many as 8% of nonselected patients. In a study by Christoph et al using MSCT scanning, an incidence of 2.2% was given.…”
Section: Discussionmentioning
confidence: 99%